Musical Video in Educational Research on the Example of Analysis and Interpretation of The Last Refugee by Roger Waters - Golonka-Legut, Joanna; Pryszmont-Ciesielska, Martyna (INSTED: Interdisciplinary Studies in Education & Society, 2018)
For the last dozen or so years the area of social research has expanded. This is connected to different cognitive challenges taken up by researchers. As for educational research, we can notice, amongst others, a strong interest in visual aspects of education, that are associated with the (re)cognition of educational potential of everyday life. With this perspective, it is worth having a look at pop culture which is not only a product but also a natural component of everyday reality. This text is an attempt to understand music video as a culture text with a narrative, which should be seen as an independent audio-visual form. A study ona video clip in educational research is proposed. An attempt to understand the nature and to (re)cognizemusic video as a source of knowledge will be made through analysis and interpretation of certain visualmaterials ? an existing research document ? the video clip to The Last Refugee by Roger Waters. The wholestudy is conducted and discussed from the andragogical perspective.